Development of Nanoporous AAO Membrane for Nano Filtration Using the Acoustophoresis Method - Yatinkumar Patel; Giedrius Janusas; Arvydas Palevicius; Andrius Vilkauskas (Sensors, 2020)
A concept of a nanoporous anodic aluminum oxide (AAO) membrane as a vibro-active micro/nano-filter in a micro hydro mechanical system for the filtration, separation, and manipulation of bioparticles is reported in this paper. For the fabrication of a nanoporous AAO, a two-step mild anodization (MA) and hard anodization (HA) technique was used. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to analyze the surface morphology of nanoporous AAO. A nanoporous structure with a pore diameter in the range of 50–90 nm, an interpore distance of 110 nm, and an oxide layer thickness of 0.12 mm with 60.72% porosity was obtained. Fourier-transform infrared spectroscopy (FTIR) and energy-dispersive X-ray spectroscopy (EDS) were employed to evaluate AAO chemical properties. The obtained results showed that the AAO structure is of hexagonal symmetry and showed where Al2O3 is dominant. The hydrophobic properties of the nanoporous surface were characterized by water contact angle measurement. It was observed that the surface of the nanoporous AAO membrane is hydrophilic. Furthermore, to determine whether a nanomembrane could function as a vibro-active nano filter, a numerical simulation was performed using COMSOL Multiphysics 5.4 (COMSOL Inc, Stockholm, Sweden). Here, a membrane was excited at a frequency range of 0–100 kHz for surface acoustics wave (SAW) distribution on the surface of the nanoporous AAO using a PZT 5H cylinder (Piezo Hannas, Wuhan, China). The SAW, standing acoustic waves, and travelling acoustic waves of different wavelengths were excited to the fabricated AAO membrane and the results were compared with experimental ones, obtained from non-destructive testing method 3D scanning vibrometer (PSV-500-3D-HV, Polytec GmbH, Waldbronn, Germany) and holographic interferometry system (PRISM, Hy-Tech Forming Systems (USA), Phoenix, AZ, USA). Finally, a simulation of a single nanotube was performed to analyze the acoustic pressure distribution and time, needed to center nanoparticles in the nanotube.